The relation between cognitive-behavioural responses to symptoms in patients with long term medical conditions and the outcome of cognitive behavioural therapy for fatigue – A secondary analysis of four RCTs. (February 2023) - de Gier, M.; Picariello, F.; Slot, M.; Janse, A.; Keijmel, S.; Menting, J.; Worm-Smeitink, M.; Beckerman, H.; de Groot, V.; Moss-Morris, R.; Knoop, H.
Abstract: Background: Cognitive behavioural therapy (CBT) is effective in reducing fatigue across long-term conditions (LTCs). This study evaluated whether cognitive and behavioural responses to symptoms: 1) differ between LTCs and 2) moderate and/or mediate the effect of CBT on fatigue. Method: Data were used from four Randomized Controlled Trials testing the efficacy of CBT for fatigue in Chronic Fatigue Syndrome/ME (N = 240), Multiple Sclerosis (N = 90), Type 1 Diabetes Mellitus (N = 120) and Q-fever fatigue syndrome (N = 155). Fatigue severity, assessed with the Checklist Individual Strength, was the primary outcome. Differences in fatigue perpetuating factors, assessed with the Cognitive Behavioural Responses to Symptoms Questionnaire (CBRQ), between diagnostic groups were tested using ANCOVAs. Linear regression and mediation analyses were used to investigate moderation and mediation by CBRQ scores of the treatment effect. Results: There were small to moderate differences in CBRQ scores between LTCs. Patients with higher scores on the subscales damage beliefs and avoidance/resting behaviour at baseline showed less improvement following CBT, irrespective of diagnosis. Reduction in fear avoidance, catastrophising and avoidance/resting behaviour mediated the positive effect of CBT on fatigue across diagnostic groups. Discussion: The same cognitive-behavioural responses to fatigue moderate and mediate treatment outcome across conditions, supporting a transdiagnostic approach to fatigue. Highlights: Similar beliefs and behaviour moderate effect of CBT on fatigue across conditions. The mediators of the effect of CBT on fatigue are also similar across conditions. The findings support a transdiagnostic approach in the treatment of fatigue.